ESTUDIO DEL COMPLEJO AMARILLO VANADOMOLIBDOFOSFÓRICO PARA EL ANÁLISIS DE FÓSFORO EN SUELOS - Carrasquero, Armando; Adams, Melitón (Venesuelos, 2011)
Se estudió el complejo amarillo vanadomolibdofosfórico a fin de determinar la relación estequiométrica entre vanadatos y molibdatos en el heteropolicomplejo. El espectro de absorción no mostró bandas entre los 400 nm y 600 nm, mientras que la representación gráfica del logaritmo de la absorbancia frente a la longitud de onda presentó curvas debidas a la formación de más de un complejo. Al aplicar el método de la relación molar fue posible detectar la presencia de dos especies absorbentes con relaciones vanadato/molibdato de 1/8 y 1/2. Única-mente el complejo con relación molar 1/2 obedece la ley de Beer. El fósforo de los suelos Danta, Upata y Guanipa fue ex-traído con la solución extractora Carolina del Norte y se efectuó el estudio siguiendo el mismo procedimiento que en las so-luciones puras, detectándose la presencia de los dos complejos ya descritos. La longitudes de onda de 400 y 440 nm fueron las más adecuadas para la cuantificación de P, mientras que a 460 se observó un comportamiento errático atribuible a los bajos valores de absorbancia que se miden a esa longitud de onda. Palabras Claves: Fósforo, Fotocolorimetría, Método amarillo, Ácido vanadomolibdofosfórico, Relación molar. Abstract The vandomolibdophosphoric yelow complex was studied in order to determine the stechiometric ratio between vanadates and molibdates. Absorption spectra did not show a maximum between 400 nm and 460 nm. A plot of log(Absorbance) aga-inst wavelength showed curves due to formation of several complexes. Applying the method of molar ratios it was possible to detect two complexes with vanadate/molibdate ratios of 1/8 and 1/2. Only this last complex gives a linear plot when absorbance is represented against P concentration. P from Danta, Upata and Guanipa soils, were extracted with North Caroline solution, and the study of the complex, was carried out with a similar procedure to pure P solutions. The two complexes described above were detected. Wavelengths of 400 nm and 440 nm were the most useful for P determinations, while at 460 nm erratic behaviors were observed which might be due to low absorbances values measured at these wavelength. Key words: Phosphorus, Photocholorimetry, Yellow method, Vanadomolibdophosphoric acid, Molar ratio. Abstract The vandomolibdophosphoric yelow complex was studied in order to determine the stechiometric ratio between vanadates and molibdates. Absorption spectra did not show a maximum between 400 nm and 460 nm. A plot of log(Absorbance) against wavelength showed curves due to formation of several complexes. Applying the method of molar ratios it was possible to detect two complexes with vanadate/molibdate ratios of 1/8 and 1/2. Only this last complex gives a linear plot when absorbance is represented against P concentration. P from Danta, Upata and Guanipa soils, were extracted with North Caroline solution, and the study of the complex, was carried out with a similar procedure to pure P solutions. The two complexes described above were detected. Wavelengths of 400 nm and 440 nm were the most useful for P determinations, while at 460 nm erratic behaviors were observed which might be due to low absorbances values measured at these wavelength. <span style="line-height: 115%; font-family: "Arial","sans-serif"; font-size: 10pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-language: EN-US; mso-fareast-theme-font: minor-latin; mso-bidi-language: AR-SA;" lang="EN-US">Key words: Phosphorus, Photocholorimetry, Yellow method, Vanadomolibdophosphoric acid, Molar ratio.